EKSISTENSI HARTA DALAM ISLAM (SUATU KAJIAN ANALISIS TEORITIS) - Rizal, Rizal (Jurnal Penelitian, 2015)
THE EXISTENCE OF PROPERTY IN ISLAM (A Study of  Theoretical Analysis). Humans have a natural tendency trying to take control and own property as much as possible. In a hadith of the Prophet, explained that the man was not satisfied with his wealth despite a valley-shaped gold so that he died. In fact, al-Quran and al- Sunnah forcefully argued that the property should not move from one person to another, but in a way that justified by syarak namely through trades or transactions based on consensual. The use of property in Islam should always be in the service of God and utilized in order taqarrub (closer) to Allah. Utilization of personal property must not only for the owner’s personal possessions, but also used for social functions in order to help fellow human beings. Islam has given special attention to the property in terms of both how to obtain and use that property owned it has a value of worship with Allah in order to achieve a happier life in the hereafter. A Muslim is commanded to make a living and generate wealth by striving mightily. Islam has given special attention to the property in terms of  both ways. How actually the concept of  property in Islam, then the following study will explain it.keywords: Hidden Existence, Ownership, Happiness.Manusia memiliki fitrah berupaya untuk menguasai dan memiliki harta sebanyak mungkin. Dalam sebuah hadith Rasulullah saw., dijelaskan bahwa manusia itu tidak akan puas dengan hartanya walaupun berbentuk satu lembah emas sehingga dia mati. Malahan al-Quran dan al-Sunnah dengan tegas menjelaskan bahwa harta tidak boleh berpindah milik dari seorang kepada orang yang lain melainkan dengan cara yang dibenarkan oleh syarak yaitu melalu perdagangan atau transaksi yang didasari atas suka sama suka. Penggunaan harta dalam ajaran Islam harus senantiasa dalam pengabdian kepada Allah dan dimanfaatkan dalam rangka taqarrub (mendekatkan diri) kepada Allah. Pemanfaatan harta pribadi tidak boleh hanya untuk pribadi pemilik harta, melainkan juga digunakan untuk fungsi sosial dalam rangka membantu sesama manusia. Islam telah memberikan perhatian khusus terhadap harta baik dari segi cara mendapatkannya maupun penggunaannya sehingga harta yang dimiliki itu mempunyai nilai ibadah di sisi Allah dalam rangka pencapaian kehidupan yang lebih bahagia di akhirat. Seorang Muslim diperintahkan untuk mencari nafkah dan menghasilkan harta dengan berjuang sekuat tenaga. Islam telah memberikan perhatian khusus terhadap harta baik dari segi cara Bagaimanakah sebetulnya konsep harta dalam Islam, maka kajian berikut akan menjelaskannya.kata kunci: Eksistensi Harta, Kepemilikan, kebahagiaan.